Further epidemiological survey for atovaquone resistant related gene of Babesia gibsoni in Japan during 2015–2018 - IGUCHI, Aiko; SOMA, Takehisa; XUAN, Xuenan (Journal of Veterinary Medical Science, 2020)
A single-nucleotide polymorphism causing the replacement of methionine with isoleucine (M121I) in cytochrome b of Babesia gibsoni has been reported to reduce the susceptibility to atovaquone (ATV) in B. gibsoni infection. In our previous study, B. gibsoni with M121I was suggested to exist in nature. Thus, further examinations were performed. In total, 105 genomic DNA samples from B. gibsoni-infected dogs were collected from western (98 samples from 15 prefectures) and eastern areas (7 samples from 4 prefectures) in Japan. The M121I variant population was identified using allele-specific real-time PCR: it was then detected in nine samples (8.57%), which was higher than that in the previous study (4.11%). Although there are unclear points, such as the history of ATV usage, careful attention should be given to emerging ATV resistance.